Hematological and Anthropometric features of patients with Knee Osteoarthritis - Muhammad Amir, Hafiz Qazi; Jabeen, Zohra; Khan, Sulhera; Sultana, Sarwat; Khan, Marium; Tariq, Anas Bin (Bangladesh Journal of Medical Science, 2022)
Objectives:Osteoarthritis (OA) is leadingcauseof decline in physical activity. The study objectiveswere to evaluate hematological and anthropometric features in knee OA. Methodology: This case control study from March 2019 to August 2019 on patients attending general outpatient department ofNaz MemorialHospital Karachi. Patients above 18 years of either gender, diagnosed as either knee OA on X-ray knee were included. Patients with positive family history,heavy lifting workers, and women on hormonal replacement therapy were excluded. SPSS version 23.0 was used for data analysis. Chi-square test was applied OA and control group keeping p-value of <0.05 as significant. Results:From 100 OA patients, 22 were below 50 years, 37 between 51-60, 31 patients between 61-70 and 10 patients above 71. Mean age of patients was 56.77 ± 11.26 years. Mean BMI of OA and control group was 30.24 ± 8.98 kg/m2 and 26.64 ± 6.24 kg/m2 (p-0.04). Mean hemoglobin of OA and control group were 11.20 ± 1.24 gm/ dl and13.3 ± 2.24 gm/dl (p-0.04). Mean total cholesterol of OA and control group was 158.34 ± 47.83 mg/dl and 137.25 ±51.22 mg/dl (p-0.05). Mean low density lipoprotein of OA and control group was 123.78 ± 27.29 mg/dl and 111.31 ± 24.39 mg/dl (p-0.05). Conclusion: Age, obesity, hemoglobin, total cholesterol, low density lipoprotein and blood glucose was found to be substantially higher among OA patients when compared with that of controls. Females and older aged patients with bilateral joint involvement were reportedly more frequently with OA. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 682-687